1999
DOI: 10.1080/00071669987205
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant systems of the avian embryo: Tissue-specific accumulation and distribution of vitamin E in the turkey embryo during development

Abstract: Tissue-specific accumulation of tocopherols and tocotrienols in turkey tissues during embryonic development and their susceptibility to lipid peroxidation were investigated. Fertile turkey eggs were incubated using standard commercial conditions. Embryonic tissues were collected at 16, 22, 25 d of incubation and from day-old poults (referred to as day 29) and alpha-; beta- + gamma- and delta-tocopherols and respective tocotrienols were analysed by HPLC. A turkey diet provided to the parent hens contained the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Antioxidants in the animal body work together as the so called “antioxidant system” to prevent damaging effects of free radicals and toxic products of their metabolism. The chick’s antioxidant system includes enzymes (e.g., superoxide dismutase, glutathione peroxidase, glutathione reductase, and catalase) and molecules (e.g., glutathione, vitamin A and E, and carotenoids) [ 30 , 31 ]. Antioxidants are needed to protect chicks from oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants in the animal body work together as the so called “antioxidant system” to prevent damaging effects of free radicals and toxic products of their metabolism. The chick’s antioxidant system includes enzymes (e.g., superoxide dismutase, glutathione peroxidase, glutathione reductase, and catalase) and molecules (e.g., glutathione, vitamin A and E, and carotenoids) [ 30 , 31 ]. Antioxidants are needed to protect chicks from oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few days of embryonic development, VE in the embryonic tissues, apart from brain, increased rapidly (Gaál et al, 1995;Noble et al, 1993;Surai et al, 1996;Surai, Sparks, & Noble, 1999b), and increasing maternal VE supplementation could increase VE concentration in the tissues of newly hatched chicks (Surai, 2000;Surai, Noble, et al, 1999;Tsai et al, 2008), a fact that could be related to the increased tissue T-AOC of newly hatched chicks in the present study, which was in agreement with previous findings (Ren, Wang, et al, 2016). Compared with the other major tissues of newly hatched chick, brain was more susceptible to lipid peroxidation (Surai, Noble, et al, 1999), due to its higher levels of polyunsaturated fatty acids (Maldjian, Cristofori, Noble, & Speake, 1996) and lower concentration of antioxidant components (Gaál et al, 1995;Surai et al, 1996).…”
mentioning
confidence: 99%
“…These results showed that there might be a relation between the superoxide scavenging activity of Chinese medicine and its function. As reported in recent literature, the assimilation and metabolism of natural substances such as food, 16) vitamin E, 17) quercetin 18) and ‰avo-noids, 19,20) play a key role in the actual physiological events. Therefore, in order to conˆrm the relationship between the superoxide scavenging activity of Chinese medicine and its function, it is necessary to investigate the assimilation and metabolism of the components of Chinese medicines, and this is a subject of future research.…”
Section: Results and Discussion Esr Spin-trappingmentioning
confidence: 99%